Key contextual success factors for employee innovative behavior: A study in a foreign manufacturing subsidiary in China - Wenqian Zhou; Vivek K. Velamuri (Cogent Business & Management, 2018)
Employee innovative behavior has been recognized as a key enabler for competitiveness in China. As more and more foreign multinational companies (MNCs) are setting up innovation activities in China, fostering employee innovative behavior is playing an increasingly central role in their development strategies. However, while there is an abundance of literature on contextual success factors to foster employee innovative behavior set in Western contexts, there has been little attention on the impact of culture-specifics in China. Also, there has been limited effort to determine the relative importance of the factors and define which ones are key. We address these gaps by conducting a Delphi study set in a foreign manufacturing subsidiary in China. Among a list of 24 success factors identified in extant literature, our results reveal reward and pay, cross-functional cooperation and company innovation strategy as the three most important factors to foster employee innovative behavior in China. We discuss these factors as to why they play a vital role for Chinese employees and finally we provide practical suggestions for implementing them. These include the set up of transparent guidelines for rewards, enhancing cross-functional cooperation and setting aligned goals among different functions.
Keywords: 650